A Neuroimaging Preparation Protocol Tailored for Autism. Issue 1 (4th November 2020) - Tziraki, Maria; Garg, Shruti; Harrison, Emma; Wright, Neville B.; Hawkes, Rob; Akhtar, Kapasi; Green, Jonathan; Stivaros, Stavros
Abstract : Abstract: This paper describes the key basic elements required for a successful multi‐parametric MRI data acquisition in awake children with autism. The procedure was designed by taking into account methodological challenges arising from the acquisition of Resting State fMRI (RS fMRI) data, and factors such as cost, time, and staff availability. The ultimate aim was to prepare an imaging preparation protocol with high transferability to the whole autism spectrum, adaptable for use in a multi‐site research with multiple time points. As part of a randomized pharmaco‐intervention study, 31 children aged 4–10 years with Neurofibromatosis 1 and autism underwent MR imaging at baseline and end of intervention. The protocol consisted of tailored habituation instructions including gradual exposure to scanner noise, a social stories booklet, positive incentive strategies, and Play Therapy support. Success rate for initial acquisition was 71% for GABA+ MR spectroscopy at either location, 87% for perfusion, and 67% for diffusion assessment, and 71% for RS fMRI. Qualitative data indicated that 84% parents found the habituation protocol helpful. Lay Summary: Here we describe a protocol for brain Magnetic Resonance Imaging (MRI) tailored for children with ASD to help reduce stress and avoid sedation during scanning. This procedure can make advanced medical imaging more accessible and promote a better MRI experience for families of children with ASD.